NOx depolluting performance of photocatalytic materials in an urban area – Part I: Monitoring ambient impact. (15th April 2021) - Fernández-Pampillón, Jaime; Palacios, Magdalena; Núñez, Lourdes; Pujadas, Manuel; Sanchez, Beatriz; Santiago, Jose Luis; Martilli, Alberto
Abstract: In the framework of the LIFE MINOx -STREET European project (co-financed by the EU), a commercial photocatalytic product consisting of a TiO2 -based water solution was implemented and tested on the bituminous asphalt of a main road of the municipality of Alcobendas (Community of Madrid, Spain), covering an area of approximately one thousand square meters both ways. This coating material was selected after rigorous laboratory assays carried out on a variety of commercial photocatalytic products. An expressly-designed experimental system has allowed to evaluate during 41 days the NOx depolluting ability of the photocatalytic material in that urban scenario. NOx ambient concentrations were monitored at several points located along the longitudinal axis of the road, both inside and outside the area treated with the photocatalytic material. Moreover, meteorological and ambient parameters at building's roof height were monitored to document the boundary conditions in the experimental area. Even though the selected photocatalytic material showed a remarkable surface deposition velocity (7.2 10 −3  m s −1 ) in laboratory tests and although the experimental deployment was carefully designed and implemented to robustly compare control and test scenarios with a high time and spatial resolution, when analyzing average NOx concentrations under filtered optimal ambient conditions to guarantee the photocatalytic effect to be maximum, no clear trend were observed in the ambient NOx levels that could be unequivocally associated with the sink effect induced by the photocatalytic material. The results have shown that the NOx gradients formed along the road were quite large even without photocatalytic coating, reflecting a complex atmospheric reality far from a homogeneous behaviour along the street, which made extremely difficult to observe the weak NOx sink effect existing. In fact, taking into account the precision of the experimental system, the potential environmental NOx purification capacity, if it had existed, would have had to be greater than 3% to be observed under the experimental conditions. This finding agrees with the estimates made by means of a simple but consistent first-order kinetic calculation for which an environmental reduction of NOx of less than 1% was obtained. All the collected data have given detailed valuable information for evaluating the results provided by a mathematical model capable of simulating the dispersion of air pollutants at urban street scale. As it is presented in the Part II of this study, these simulations have permitted to estimate accurately the impact on air quality of the use of this remediation technology not only under the actual experimental conditions but also in other urban scenarios. Highlights: Photocatalytic materials need to be investigated to play a significant role in mitigating urban NOx pollution. Urban air quality changes at local scale induced by a photoactive bituminous pavement are assessed. Robust experimental campaigns are needed for demonstrating air-purifying ability of photocatalytic materials at real scale. Ensuring that observed NOx  ambient reduction is induced by the applied photoactive surfaces involves great difficulty. No significant improvement in air quality is observed even near the photocatalytic road in the studied street canyon.